2019
DOI: 10.3389/fendo.2019.00617
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effect of Metformin on Cancer: An Umbrella Review

Abstract: Background: Metformin has been reported to possess anti-cancer properties in addition to glucose-lowering activity and numerous systematic reviews and meta-analyses have studied the association between metformin use and cancer incidence or survival outcomes. We performed an umbrella review to assess the robustness of these associations to facilitate proper interpretation of these results to inform clinical and policy decisions.Methods: We searched PubMed and Embase systematic reviews and meta-analyses investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
90
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 63 publications
0
90
0
2
Order By: Relevance
“…It has been reported that diabetic patients with metformin treatment had a low incidence of cancer . There exists a close correlation among metformin treatment and cancer incidence or patient survival . For the molecular mechanism of metformin in cancer treatment, it has been reported to inactivate STAT3 or NF‐κB, preventing IL‐6‐induced breast cancer progression .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that diabetic patients with metformin treatment had a low incidence of cancer . There exists a close correlation among metformin treatment and cancer incidence or patient survival . For the molecular mechanism of metformin in cancer treatment, it has been reported to inactivate STAT3 or NF‐κB, preventing IL‐6‐induced breast cancer progression .…”
Section: Discussionmentioning
confidence: 99%
“…3 There exists a close correlation among metformin treatment and cancer incidence or patient survival. [4][5][6] For the molecular mechanism of metformin in cancer treatment, it has been reported to inactivate STAT3 or NF-κB, preventing IL-6-induced breast cancer progression. 7 In prostate cancer, lung cancer, colon cancer or breast cancer patients with T2DM, metformin has been shown to reduce the development of tumor and prolong the survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies suggested the anticancer property of drug 24. The drug 24 at the dose of 250-500 mg/day has been shown to reduce the risk of cancer as well as its daily dose reduces the incidence of gastrological cancer in patients with diabetes [59,60].…”
Section: Introductionmentioning
confidence: 99%